Perirhinal cortex and temporal lobe epilepsy - Biagini, Giuseppe; D'Antuono, Margherita; Benini, Ruba; de Guzman, Philip; Longo, Daniela; Avoli, Massimo (Frontiers in Cellular Neuroscience, 2013)
The perirhinal cortex—which is interconnected with several limbic structures and is intimately involved in learning and memory—plays major roles in pathological processes such as the kindling phenomenon of epileptogenesis and the spread of limbic seizures. Both features may be relevant to the pathophysiology of mesial temporal lobe epilepsy that represents the most refractory adult form of epilepsy with up to 30% of patients not achieving adequate seizure control. Compared to other limbic structures such as the hippocampus or the entorhinal cortex, the perirhinal area remains understudied and, in particular, detailed information on its dysfunctional characteristics remains scarce; this lack of information may be due to the fact that the perirhinal cortex is not grossly damaged in mesial temporal lobe epilepsy and in models mimicking this epileptic disorder. However, we have recently identified in pilocarpine-treated epileptic rats the presence of selective losses of interneuron subtypes along with increased synaptic excitability. In this review we: (i) highlight the fundamental electrophysiological properties of perirhinal cortex neurons; (ii) briefly stress the mechanisms underlying epileptiform synchronization in perirhinal cortex networks following epileptogenic pharmacological manipulations; and (iii) focus on the changes in neuronal excitability and cytoarchitecture of the perirhinal cortex occurring in the pilocarpine model of mesial temporal lobe epilepsy. Overall, these data indicate that perirhinal cortex networks are hyperexcitable in an animal model of temporal lobe epilepsy, and that this condition is associated with a selective cellular damage that is characterized by an age-dependent sensitivity of interneurons to precipitating injuries, such as status epilepticus.